Development and Adhesion Strength of Plasma-Sprayed Thermal Barrier Coating on the Cast Iron Substrate - Haridasa Nayak,; N Krishnamurthy,; Shailesh R A, (International Journal of Integrated Engineering, 2021)
In the present scenario, the atmospheric plasma spray is used as a very important and effective weapon to produce the thermal barrier coating (TBC) on the substrate which will impart required surface characteristics to the components which are demanded by the industry. The TBC is used to impart the required characteristic such as wear, corrosion and thermal resistance to the hot section component where these will undergo severe service condition at elevated temperature. Research is carried out to replace the conventional liners in the I.C Engine by the thermal barrier coated ceramic liner. To achieve this, in this work Cast Iron substrate is used and it has been coated with a thermal barrier coating with the help of Atmospheric plasma spraying. These consisting of equal-proportion YSZ and pure alumina as topcoat ceramic material and in-between these topcoat and substrate there will be two bond coat first bond coat is Nickel Iron Aluminium Composite Powder (Metco 452) between the substrate and second bond coat. Second is  Alumina Nickel Aluminide powder blend (Metco 410 NS) between the topcoat and first bond coat. Coatings were subjected to microstructure analysis, porosity and adhesion strength. In this work, top coating thickness ie. 300Âµm exhibits more percentage of porosity ie.4.2% than other two coating thickness 200 and 100 Âµm  3.9% and 3.5% respectively. The bond coat will possess porosity percentage of  4.0 %, 3.5 % and 3 % for C3, C2 and C1 respectively. The adhesion strength test of the coatings was conducted and determined by the help of varying the topcoat thickness from 100Âµm to 300 Âµm with a step of 100 Âµm. In this work, it was established that the topcoat with the 100 Âµm exhibits the very good bond strength 70.81 MPa when compared with other two coating thickness 200Âµm and 300 Âµm have the adhesion strength 69.1 MPa and 65.52 MPa respectively. ASTM C 633 standard is used to prepare and conduct the test.